Efficacy of a Carrageenan gel Against Transmission of Cervical HPV (CATCH): interim analysis of a randomized, double-blind, placebo-controlled, phase 2B trial. (February 2019) - Magnan, S.; Tota, J.E.; El-Zein, M.; Burchell, A.N.; Schiller, J.T.; Ferenczy, A.; Tellier, P.-P.; Coutlée, F.; Franco, E.L.; ,; Rodrigues, A.; Morykon, N.; et al.
Abstract: Objectives: To evaluate the efficacy of a carrageenan-based lubricant gel in reducing the risk of genital human papillomavirus (HPV) infections in women. Methods: We conducted a planned interim analysis of a randomized, double-blind, placebo-controlled, phase 2B trial. Women aged 18 years and older were randomly assigned (1:1) to a carrageenan-based gel or a placebo gel to be self-applied every other day for the first month and before and after each intercourse during follow-up. Assessments were performed at 0.5, 1, 3, 6, 9 and 12 months. The primary outcome was incidence of a new infection by an HPV type that was not present at baseline. Intention-to-treat analyses were performed. Results: Between January 2013 and June 2017, a total of 280 participants were randomly assigned to the carrageenan ( n  = 141) or the placebo ( n  = 139) arm. All participants were included in safety analyses, but three (1%) were excluded from efficacy analyses (HPV results unavailable for two participants in the carrageenan and one participant in the placebo arm). The median follow-up time was 9.2 months (interquartile range, 1.9–13.2 months). A total of 59 (42%) of 139 participants in the carrageenan arm and 78 (57%) of 138 participants in the placebo arm became infected by at least one new HPV type (hazard ratio = 0.64, 95% confidence interval = 0.45–0.89, p 0.009). A total of 62 (44%) of 141 participants in the carrageenan arm versus 43 (31%) of 139 participants in the placebo arm reported an adverse event (p 0.02), none of which was deemed related to the gels. Conclusions: Our trial's interim analysis suggests that using a carrageenan-based lubricant gel can reduce the risk of genital HPV infections in women.